Enhanced iceberg discharge in the western North Atlantic during all Heinrich events of the last glaciation - Zhou, Yuxin; McManus, Jerry F.; Jacobel, Allison W.; Costa, Kassandra M.; Wang, Shouyi; Alvarez Caraveo, Blanca (Earth and Planetary Science Letters, 2021)
A series of catastrophic iceberg and meltwater discharges to the North Atlantic, termed Heinrich events, punctuated the last ice age. During Heinrich events, coarse terrigenous debris released from the drifting icebergs was preserved in deep-sea sediments, serving as an indicator of iceberg passage. Quantifying the vertical flux of ice-rafted debris (IRD) in open-ocean settings can resolve questions regarding the timing and spatial variation in ice sheet calving intensity. In this study, 230Thxs-based IRD flux throughout the last glacial period was measured in a deep-sea sediment core from the western North Atlantic, and complemented by data spanning 0-32 ka from a sediment core in the Labrador Sea. The cores were recovered from sites downstream from Hudson Strait, a likely conduit for icebergs calving from the Laurentide ice sheet (LIS). We compare our results with equivalent existing data from the eastern North Atlantic and show that the two cores in our study have higher IRD fluxes during all Heinrich events, notably including events H3 (∼31 ka) and H6 (∼60 ka). This study demonstrates that the LIS played a role in all Heinrich events, and raises the likelihood that a single mechanism can account for the genesis of these events.
Keywords: Heinrich event; IRD flux; thorium normalization; western north atlantic

Carbon isotope evidence for a northern source of deep water in the glacial western North Atlantic - Keigwin, Lloyd D.; Swift, Stephen A. (Proceedings of the National Academy of Sciences, 2017)
The prevailing view of western Atlantic hydrography during the Last Glacial Maximum (LGM) calls for transport and intermixing of deep southern and intermediate northern end members. However, δ13C and Δ14C results on foraminifera from a sediment core at 5.0 km in the northern subtropics show that there may have also been a northern source of relatively young, very dense, nutrient-depleted water during the LGM (18 ky to 21 ky ago). These results, when integrated with data from other western North Atlantic locations, indicate that the ocean was poorly ventilated at 4.2 km, with better ventilation above and below that depth. If this is a signal of water mass source and not nutrient storage, it would indicate that a previously unrecognized deep water end member originated along the western margin of the Labrador Sea, analogous to dense water formation today around Antarctica and in the Okhotsk Sea.
Keywords: carbon isotopes; Last glacial maximum; ocean ventilation; oxygen isotopes; western north atlantic

Radiocarbon and stable isotope constraints on Last Glacial Maximum and Younger Dryas ventilation in the western North Atlantic - Keigwin, L. D. (Paleoceanography, 2004)
[1] Foraminiferal abundance, C-14 ventilation ages, and stable isotope ratios in cores from high deposition rate locations in the western subtropical North Atlantic are used to infer changes in ocean and climate during the Younger Dryas (YD) and Last Glacial Maximum (LGM). The delta(18)O of the surface dwelling planktonic foram Globigerinoides ruber records the present-day decrease in surface temperature (SST) of similar to 4 degreesC from Gulf Stream waters to the northeastern Bermuda Rise. If during the LGM the modern delta(18)O/salinity relationship was maintained, this SST contrast was reduced to 2 degreesC. With LGM to interglacial delta(18)O changes of at least 2.2parts per thousand, SSTs in the western subtropical gyre may have been as much as 5 degreesC colder. Above similar to 2.3 km, glacial delta(13)C was higher than today, consistent with nutrient-depleted ( younger) bottom waters, as identified previously. Below that, delta(13)C decreased continually to - 0.5parts per thousand, about equal to the lowest LGM delta(13)C in the North Pacific Ocean. Seven pairs of benthic and planktonic foraminiferal C-14 dates from cores > 2.5 km deep differ by 1100 +/- 340 years, with a maximum apparent ventilation age of similar to 1500 years at 4250 m and at similar to 4700 m. Apparent ventilation ages are presently unavailable for the LGM < 2.5 km because of problems with reworking on the continental slope when sea level was low. Because LGM δC-13 is about the same in the deep North Atlantic and the deep North Pacific, and because the oldest apparent ventilation ages in the LGM North Atlantic are the same as the North Pacific today, it is possible that the same water mass, probably of southern origin, flowed deep within each basin during the LGM. Very early in the YD, dated here at 11.25 +/- 0.25 ( n = 10) conventional C-14 kyr BP ( equal to 12.9 calendar kyr BP), apparent ventilation ages < 2.3 km water depth were about the same as North Atlantic Deep Water today. Below similar to 2.3 km, four YD pairs average 1030 +/- 400 years. The oldest apparent ventilation age for the YD is 1600 years at 4250 m. This strong contrast in ventilation, which indicates a front between water masses of very different origin, is similar to glacial profiles of nutrient-like proxies. This suggests that the LGM and YD modes of ocean circulation were the same.
870dfTimes Cited:72 Cited References Count:60
Keywords: benthic foraminifera; deep-sea sediments; ice-age; Ocean circulation; ocean ventilation; pacific-ocean; radiocarbon; SARGASSO SEA; southern-ocean; Thermohaline circulation; united-states; water circulation; western north atlantic